Analysis of Iliac Artery Geometric Properties in Fenestrated Aortic Stent Graft Rotation. (April 2018) - Doyle, Matthew G.; Crawford, Sean A.; Osman, Elrasheed; Eisenberg, Naomi; Tse, Leonard W.; Amon, Cristina H.; Forbes, Thomas L.
Introduction: A complication of fenestrated endovascular aneurysm repair is the potential for stent graft rotation during deployment causing fenestration misalignment and branch artery occlusion. The objective of this study is to demonstrate that this rotation is caused by a buildup of rotational energy as the device is delivered through the iliac arteries and to quantify iliac artery geometric properties associated with device rotation. Methods: A retrospective clinical study was undertaken in which iliac artery geometric properties were assessed from preoperative imaging for 42 cases divided into 2 groups: 27 in the nonrotation group and 15 in the rotation group. Preoperative computed tomography scans were segmented, and the iliac artery centerlines were determined. Iliac artery tortuosity, curvature, torsion, and diameter were calculated from the centerline and the segmented vessel geometry. Results: The total iliac artery net torsion was found to be higher in the rotation group compared to the nonrotation group (23.5 ± 14.7 vs 14.6 ± 12.8 mm −1 ; P = .05). No statistically significant differences were found for the mean values of tortuosity, curvature, torsion, or diameter between the 2 groups. Conclusion: Stent graft rotation occurred in 36% of the cases considered in this study. Cases with high iliac artery total net torsion were found to be more likely to have stent graft rotation upon deployment. This retrospective study provides a framework for prospectively studying the influence of iliac artery geometric properties on fenestrated stent graft rotation.